Through the looking glass: methodological features of research of alternative schools - Snježana Dubovicki; Tomislav Topolovčan (University of Maribor Press, 2020)
On the basis of the analysis of the general characteristics of alternative schools and the methodology of pedagogical research, the comparison and synthesis of the obtained facts were formed. It is pointed out that in the field of pedagogy, the adoption of (positivist) methodology has become a global trend. It emphasizes the uncritical application of research tools from the corpus of quantitative methodology in research of specific educational problems, as well as in research of alternative schools in which the context of the research is significantly different than the one of the conventional public schools.